The Influence of Character Education and Attitude Cultivation on Social Development Early Childhood in Garut District - Maryani, Tina; Panji Yudha, Rivo; Yussof, Hilmy Baihaqy; Izatovna, Toyirova Shahlo (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2025)
Education is a process in the form of transfer or improvement that embraces and involves various elements in achieving the expected goals. Early Childhood Education (PAUD) is basically an education given to children, taking into account aspects of child development. At this time, children experience extraordinary growth and development, cognitively, physically, socially and emotionally. Early Childhood Education (PAUD) is held to stimulate the growth and development of children who behave dynamically in places where the environment is highly influential. The problem formulation in this study is the extent of the impact of personality formation and attitude development on promoting social and emotional development in early childhood. The purpose of this study is to investigate whether personality and attitude formation affect the promotion of socio-emotional development in early childhood. When conducting a study, the author adopts methods that appear appropriate to clarify the measurement of the final outcome of the study conducted. That is, use a quantitative research method. Conclusion of survey results: 1) The value of tcount is larger than that of ttable. This shows that character building can enhance the social and emotional development of children. 2) The value of tcount is larger than that of ttable, which indicates that the social and emotional development of the child can be improved by cultivating the attitude. 3) In computer processing based on SPSS calculations, Fcount is larger than Ftable, showing that the combination of personality and attitude education can improve the social and emotional development of early childhood in the Garut Distric